2017
DOI: 10.1002/jsfa.8266
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Japanese consumer gender and age on sensory attributes and preference (a case study on deep‐fried peanuts)

Abstract: In the present study, systematic statistical analysis based on collected sensory evaluation data using deep-fried peanuts was conducted and the tendency of sensory perception and preference across gender and age was clarified. These results may be useful for engineering optimal strategies to target specific segments to gain greater acceptance in the market. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The patterns of cassava leaf consumption are generally similar for males and females. Miyagi (2017) and Alamu et al (2019b) observed a similar trend where there was no significant difference between the consumer preference results of males and females.…”
Section: The Consumer Preference For Sensory Attributes By Locationsupporting
confidence: 53%
“…The patterns of cassava leaf consumption are generally similar for males and females. Miyagi (2017) and Alamu et al (2019b) observed a similar trend where there was no significant difference between the consumer preference results of males and females.…”
Section: The Consumer Preference For Sensory Attributes By Locationsupporting
confidence: 53%
“…Pleasurable tastes are preferred by humans, whereas unpleasant tastes are avoided [76]. Fried food products are widely consumed because of their typical flavor, taste, and crispy texture [77].…”
Section: Changes In Sensory Characteristicsmentioning
confidence: 99%
“…This contrasts with the fact that, generally, bitterness is a driver of disliking, as previously described. This concept has been reinforced by studies aimed at evaluating the sensory profiles of single food products [101,102,103,104,105]. For example, in [99] whole bread has been described as more bitter compared to white bread, and white bread was preferred only by medium- and super-tasters.…”
Section: Single Product Perception and Preferencementioning
confidence: 99%